Reliability Optimum Design of Spring in the Tools Storage - SUN Kui zhou; FENG Hu tian; ZHOU Jin yu (Institute of Advanced Engineering and Science, 2012)
According to the spring’s failures in the tools storage and mechnical tools locking, the thesis will discuss the reliability optimization design for spring. With the known probability characteristics of basic random parameters, the random perturbation method, the reliability theory and optimal design technology are used to give the spring reliability design problems in locking knife spring in the tools storage and mechanical tools of machining center, to put forward the practical and effective reliability-based optimization design method, which can shorten the design cycle, save the testing cost, improve the design level and the reliability of parts. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1276